Transformational Leadership and Intrinsic Motivation on Employee Performance in the Mechanical Division of Pt.Astra Internasional (Tbk) Toyota Auto 2000 Bumi Serpong Damai Branch, South Tangerang. - Ardiansyah, Fikri; Pasaribu, Veta Lidya Delimah (Westscience Press, 2024)
This study examined the impact of transformational leadership and intrinsic motivation on employee performance. A quantitative approach was adopted, employing a saturated sample consisting of all 54 employees. Data analysis involved validity and reliability tests, classical assumption checks, regression analysis, correlation coefficients, coefficients of determination, and hypothesis testing. The results revealed that transformational leadership positively influences employee performance. The regression equation Y = 37.836 + 0.115X1 indicated a weak relationship, with a correlation coefficient of 0.294. The coefficient of determination (R2) of 0.119 suggests that transformational leadership accounts for 11.9% of the variance in employee performance, while other factors explain the remaining 88.1%. Hypothesis testing further supported this relationship, with a calculated t-value of 2.680 exceeding the critical value of 1.675 (p <.05), thus confirming H1. Intrinsic motivation also demonstrated a positive impact on employee performance. This was evident in the regression equation Y = 20.529 + 0.517X2. Hypothesis testing corroborated this finding, with a calculated t-value of 3.164 surpassing the critical value of 1.675 (p <.05). Finally, the combined effect of transformational leadership and intrinsic motivation on employee performance was explored through the regression equation Y = 23.637 + 0.136X1 + 0.582X2. The coefficient of determination for this model was 0.171, indicating that these two factors collectively explain 17.1% of the variance in employee performance. H3 was accepted following an F-test that confirmed its significance (F = 5.265, p <.05).